Deskripsi Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika - Nurlaelah; Alimuddin; Ilham Minggi (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2017)
This research aimed to describe the types of errors made by students in solving mathematical problems in the Two-Linear Linear Equation System and the factors causing students to make mistakes. The research subjects consisted of 2 students of class IX.A who were selected based on how many errors were made in solving math story problems. The instrument used is a written test that contains 1 item description and interview guidelines. The errors analyzed are categorized using the Newman error category which consists of 5 errors, namely reading errors, misunderstanding, errors in transforming, processing errors and errors in writing the final answer. The results showed that based on the Newman error criteria, the errors that occurred were not being able to write down what was known and what was asked, not being able to make a mathematical model correctly, unable to use procedures, wrong in using count operations and unable to conclude the final results. The cause of students making mistakes is not understanding the information in the problem, lack of accuracy of students, and lack of skills, forgetting, and hurrying in answering questions. The results of this study are expected to add insight into the types of errors made by junior high school students in the material system of linear equations of two variables, especially in working on problems related to everyday life so that in the learning process mistakes made can be minimized immediately.